特教學校校長多元架構領導與教師工作滿意度關係之研究 - 劉貞利(Chenli Liu); 吳新傑(Jason Hsinchieh Wu) (School Administrators, 2024)
This study investigates the relationship between the multi-frame leadership of special education school principals and teachers’ job satisfaction. Principals and teachers in special education play pivotal roles in supporting students with severe and multiple disabilities. Yet, current domestic research on principals’ multi-frame leadership mostly focuses on exploring the impact on school effectiveness, and most of the research subjects are primary and secondary school principals. However, there is no research on the relationship between principal leadership and teacher job satisfaction in special education schools. Therefore, this study aims to investigate the current status of multi-frame leadership among special education school principals, teachers’ job satisfaction, and explore the relationship between the two. Utilizing a questionnaire survey method, a sample of teachers from 21 intellectual disability special education schools in Taiwan was selected. Out of 600 distributed surveys, 515 valid responses w